URGENCY OF CHARACTER EDUCATION INTEGRATION VALUE IN SCHOOL - Suriadi, Kamil, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Today the world is suffering from various diseases. Business without morality Political without principle, Education without character, sustenance without sacrifice, Humanity without merit, the devotion without faith. Today the seven mentioned above illness are causing all problems to the Nation. Everyone must decide to free the country from seven painful diseases. The idea of integrated education is not just about how to make people smart, but to make good people too. It is not just about giving people knowledge, but also helping them to translate that knowledge into true wisdom. With an integrated education, there is no division between school and community, study and human life, knowledge, and kindness. This paper contains three essentials. First, the integrative meaning of the nation's educational values. Second, the pattern of integration of the nation's educational values on learning activities in schools. Third, implications for schools, teachers, learners, and parents. This paper contains three essentials. First, the integrative meaning of educational values. Second, the integration of educational values in school activities. Third, implications for schools, teachers, learners, and parents.